A rare presentation of retroperitoneal liposarcoma presented with jejunal intussusception: An interesting radiological findings - Farehah Johari; Andee Dzulkarnaen Zakaria; Rosnelifaizur Ramely; Mohamed Arif Hameed Sultan; Muhamad Hud Muhamad Zin; Shahrunizam Awang Setia; Firdaus Hayati (Elsevier Inc, 2024)
A jejunal intussusception as a presentation of retroperitoneal liposarcoma (RLPS) is a rare occurrence. The majority of RLPS are presented as an abdominal mass, however, having a jejunal obstruction is an interesting case. The aim is to describe the management of jejunal intussusception secondary to atypical lipomatous tumours with concurrent RLPS. A 61-year-old lady presented with a sudden onset of intestinal obstruction with 1 month of constitutional symptoms and an enlarging right lumbar mass. Computed tomography showed a small bowel intussusception with diffuse peritoneal and retroperitoneal lipomatosis. Emergency exploratory laparotomy, segmental bowel resection, and partial excision of intraperitoneal mesenteric lipoma were performed. A stage En-bloc resection of the RLPS and right nephrectomy was done later. However, she refused for subsequent surgery. A complete resection is the gold standard in managing RLPS. In this report, the management is rendered not to the standard as the patient first presented with intestinal obstruction requiring emergency reduction with a piecemeal resection. A stage surgery was required to determine a promising prognosis, but the patient refused such surgery. A small bowel intussusception in adults is rare but is mostly caused by a tumor or neoplasm. Early recognition of the complexity of the case should be preempted and referred to the tertiary team for further definitive surgery. Patient exhaustion from the subsequent surgery might hamper the only management available for the case.